ENHANCING STUDENT’S LEARNING EXPERIENCE THROUGH THE USE OF ETHICAL DILEMMA IN ROLE PLAYING LEARNING MODEL AT SMKN DARANGDAN - Mulia Sari; Kokom Komalasari; Aim Abdulkarim; Khofifah Ajeng Triani; Mohammad Rian Ari Sandi; Zulfa Ajda Khoiriyah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
A crucial problem of education in Indonesia is the low quality of learning, therefore innovation in learning model is needed to solve this problem. This study investigates the enhancement of students’ learning experience through the integration of ethical dilemma within role-playing learning model as a learning innovation. Employing a mixed-methods approach, the research utilizes both quantitative and qualitative methodologies. Quantitative data were collected using a Likert-scale questionnaire, and the result were analyzed through descriptive statistics with IBM SPSS software, yielding a mean score of 3.83. According to the Likert Scale, a score within the range of 3.41 – 4.20 indicated positive agreement, demonstrating that students generally concurred that ethical dilemma in role-playing learning model positively impacted their learning experience. In the qualitative phase, data were gathered through interviews, providing deeper insights into student’s’ perspectives of their experiences. The students expressed that the role-playing model incorporating ethical dilemmas enhanced their understanding by requiring them to comprehend of knowledge, as students were able to practice real-world decision-making skills in applying. Additionally, the model also encouraged reflecting, enabling students to evaluate and discuss their chosen solutions. Conducted at SMKN Darangdan with sample of 25 students, this study concludes that using ethical dilemma in role-playing learning model effectively improves students’ learning experience, particularly in understanding, applying, and reflecting.